2008
DOI: 10.1590/s0001-37652008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and rapid titrimetric and spectrophotometric methods for the determination of stavudine in pharmaceuticals using bromate-bromide and three dyes

Abstract: Four sensitive and rapid methods for the determination of stavudine (STV) in bulk drug and in dosage forms were developed and optimized. In titrimetry, aqueous solution of STV was treated with a known excess of bromate-bromide in HCl medium followed by estimation of unreacted bromine by iodometric back titration. Spectrophotometric methods involve the addition of a measured excess of bromate-bromide in HCl medium and subsequent estimation of the residual bromine by reacting with a fixed amount of methyl orange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…One direct titrimetric method and two indirect spectrophotometric methods for the determination of amlodipine besylate (ADB) are described [32]. The methods uses bromate-bromide mixture and two-dyes, namely Methyl Orange and Indigo Carmine, as reagents.…”
Section: Pharmacological Actionmentioning
confidence: 99%
“…One direct titrimetric method and two indirect spectrophotometric methods for the determination of amlodipine besylate (ADB) are described [32]. The methods uses bromate-bromide mixture and two-dyes, namely Methyl Orange and Indigo Carmine, as reagents.…”
Section: Pharmacological Actionmentioning
confidence: 99%
“…For each experimental datum in the following experiments, in addition to those mentioned in particular, at least three values were averaged to obtain reliable data. The bromine titration in the form of the familiar potassium bromide-potassium bromate mixture has been applied to quantitate unsaturated carboncarbon double bonds for other compounds 25,26 and was applied to measure that in CSO-g-AA after some modifications. Briefly, a standard solution of potassium bromide and potassium bromate was employed in acid solution to generate bromine, which reacted with the unsaturated double bonds.…”
Section: Determination Of the Amidation Degree Of Csomentioning
confidence: 99%
“…D4T is converted to triphosphate inside the cell and cease the DNA synthesis of retroviruses via competing with reverse transcriptase enzyme inhibitory effect and incorporation into viral DNA. (Basavaiah, et al, 2008).Stavudine is a white to off-white crystalline powder. It is freely soluble in ethanol (95%) with a solubility of about 83 mg/ml in water at 23°C [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…(Basavaiah, et al, 2008).Stavudine is a white to off-white crystalline powder. It is freely soluble in ethanol (95%) with a solubility of about 83 mg/ml in water at 23°C [3] [4]. It was suggested that Stavudine can distributes into body fluid and used the non-facilitated diffusion to enter body cells [5] Figure 1: Chemical structure of Stavudine Several methods of analysis been used to determine Stavudine in biological fluids or pharmaceutical preparations.…”
Section: Introductionmentioning
confidence: 99%